2009
DOI: 10.1097/meg.0b013e328317f4b5
|View full text |Cite
|
Sign up to set email alerts
|

Patients with nonalcoholic fatty liver disease display increased serum resistin levels and decreased adiponectin levels

Abstract: NAFLD patients had lower adiponectin levels and higher resistin levels. A positive correlation was found between resistin and waist circumference, whereas a negative correlation was found between adiponectin and waist circumference, body mass index, percentage of body fat, abdominal wall fat thickness, and fasting blood glucose concentration. These data suggested that hypoadiponectinemia and hyperresistinemia might be involved in the development of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
(36 reference statements)
3
26
0
1
Order By: Relevance
“…However, we did not see decreased serum adiponectin or an increase in other proinflammatory cytokines levels in our study. Resistin has been shown to be elevated in NAFLD subjects and is associated with increased insulin resistance and NF-kB activation (48, 49). Moreover, our novel hepatic transcriptome profiling results implicate activation of the MAPK and NF-kB inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not see decreased serum adiponectin or an increase in other proinflammatory cytokines levels in our study. Resistin has been shown to be elevated in NAFLD subjects and is associated with increased insulin resistance and NF-kB activation (48, 49). Moreover, our novel hepatic transcriptome profiling results implicate activation of the MAPK and NF-kB inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted that obesity, particularly central obesity is a risk factor strongly associated with NAFLD [17-19]. About half of the literatures support the notion that serum resistin increases are accountable for the obesity and insulin resistance [20-23], while the other half showed the opposite: resistin is downregulated in obese subjects and resistin had no correlation with insulin resistance [8,10,24]. Resistin is primarily secreted by monocytes or macrophages in humans [25-27].…”
Section: Discussionmentioning
confidence: 99%
“…In a second study, visceral adipose tissue expression of resistin was unchanged but serum levels of the adipocytokine were higher in patients with NASH [147]. Increased levels of resistin in NAFLD patients was shown also by other authors [106]. Moreover, among NASH patients, those with advanced fibrosis have been shown to have higher circulating resistin compared to those with less extensive fibrosis [146].…”
Section: Resistinmentioning
confidence: 53%
“…Numerous studies showed lower serum adiponectin concentrations in NAFLD patients when compared to matched controls [102][103][104][105][106] but the correlation between plasma levels of the adipocytokine and the severity of liver damage is still controversial. In one report, plasma adiponectin negatively correlated with steatosis and necroinflammation but not with the severity of fibrosis, which was predicted only by insulin resistance [102].…”
Section: Adiponectin: Clinical Correlationmentioning
confidence: 99%